THE IMPLEMENTATION OF LISTEN AND DRAW ACTIVITY TO TEACH LISTENING OF A DESCRIPTIVE TEXT TO THE SEVENTH GRADERS (RETAIN, 2015)
Abstract In teaching listening, teachers often do a monotonous activity that is a conventional way by giving worksheet to the students, playing audio, and getting the students to write their answer. As a result, the students are able to answer the questions following the audio, but they cannot complete the task and fail to understand the message delivered. To solve the problem the writer investigated the implementation of “listen and draw” activity to teach listening of a descriptive text to the seventh graders. This research is aimed to describe not only the implementation of that technique but also the students’ attitude towards the implementation of “listen and draw” activity itself. The writer used descriptive research under qualitative approach to design the research. The subject of this study was the English teacher and the seventh grade students of SMPN 4 Gresik. The data were taken from the result of the two-meeting observation and also the result of the questionnaire. The findings show the teacher conducted the teaching and learning process in three phases, i.e. pre-listening, whilst-listening, and post-listening activities and implemented the procedure of “listen and draw” activity based on the theory with some adaptations to make the activities suitable for the learning steps suggested by 2013 curriculum. The students could draw the picture completely and interpret their idea about the text played by the audio. Moreover, the students could develop their imaginations about the picture. Furthermore, from the questionnaire it is found out that most students were interested in “listen and draw” activity and indicated positive attitudes. Keywords:“Listen and draw” activity, teaching listening, descriptive text. Abstrak Dalam pengajaran mendengarkan, para guru kerap kali melakukan kegiatan yang monoton seperti cara konvensional dengan memberikan lembar pekerjaan ke peserta didik, memutar audio, dan meminta peserta didik untuk menjawab pertanyaan. Sebagai hasilnya, siswa dapat menjawab pertanyaan sesuai dengan audio akan tetapi mereka tidak dapat menyelesaikan pekerjaannya dan tidak dapat memahami pesan yang disampaikan audio. Untuk menyelesaikan masalah tersebut, penulis meneliti penerapan kegiatan “mendengar dan menggambar” untuk pengajaran mendengarkan teks deskripsi ke siswa kelas tujuh. Penelitian ini bertujuan untuk mendeskripsikan tidak hanya penerapan dari teknik tersebut, tetapi juga tanggapan siswa kepada penerapan kegiatan “mendengar dan menggambar” itu sendiri. Penulis menggunakan penelitian deskripsi dalam pendekatan kualitatif untuk merencanakan penelitian. Subyek penelitian ini merupakan guru Bahasa Inggris dan siswa kelas tujuh di SMPN 4 Gresik. Data penelitian didapat dari hasil dua kali pengamatan dan juga hasil dari kuesioner. Hasil menunjukkan bahwa guru melakukan kegiatan belajar mengajar dalam tiga sesi yaitu sebelum mendengarkan, selagi mendengarkan, dan setelah mendengarkan serta melaksanakan tata cara kegiatan “mendengarkan dan menggambar” sesuai dengan teori yang ada dengan beberapa adaptasi untuk membuat aktivitas-aktivitas tersebut cocok untuk langkah-langkah yang ada di kurikulum 2013. Selanjutnya, siswa dapat mengembangkan imajinasi mereka tentang gambar tersebut. Selain itu, kebanyakan dari siswa tertarik dengan kegiatan “mendengar dan menggambar” dan menunjukkan tanggapan yang positif. Kata Kunci: Kegiatan “mendengar dan menggambar”, pengajaran mendengarkan, teks deskripsi.